The Role Of The Anaesthetist As A Care Provider In Perianesthesia In The Operating Room At The Hospital - Emanuel Ileatan Lewar Emanuel; Putu Inge Ruth Suantika (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2021)
Introduction: Perianesthesia nurses are health professionals with specific abilities to care, treat, assist and protect patients after undergoing diagnostic or therapeutic procedures. They work closely with anesthesiologists to manage and monitor patients before, during and after anaesthetic procedures. The conditions in this practice area have a confusing role in providing anesthetic management care to patients who are unable to help themselves in anesthesia, especially in perianesthesia. Therefore, it is very important to research the role of the anesthesiologist as a care provider for perianesthesia in the operating room.Objective: The purpose of this study was to identify the role of anaesthetists as care providers for perianesthesia in the operating room. Methods: This is a descriptive exploratory research with a qualitative approach. This research consists of two stages; data collection in the first stage was carried out through in-depth interviews with anaesthetists working in the Wangaya General Hospital Denpasar operating room. In the second stage, we triangulated the data from anesthesiologists as decision-makers or doctors in charge of administering anesthesia to patients to ensure that the obtained data is consistent, convergent and valid. Qualitative data analysis is inductive; analysis is based on the obtained data, and then the data is searched repeatedly with triangulation techniques; the writing is done through narrative methods. Results: This study showed that anaesthetists at Wangaya Hospital with an educational background of Diploma III and Diploma IV Anaesthesia Nursing, and Diploma III Nursing with anaesthesiology training with Specialty Registrars, administer anaesthesia or become the care provider in pre-anaesthesia, intra-anaesthesia and post-anaesthesia based on scientific, and professional standards of anesthesiology. Conclusion : The anaesthetists can become care providers for perianesthesia in the operating room, which can be used as the first step by other researchers for further research on the effect of anaesthetic care in anaesthesia patient safety.